Single coronary ostium, unilateral pulmonary atresia and MAPCA with tetralogy of fallot in a young adult: a rare association - Vora, Keyur (International Journal of Medical Research and Review, 2016)
Tetralogy of Fallot (TOF) is the most common form of cyanotic congenital heart disease (CHD). The mortality rate in untreated patients reaches 50% by age 6 years. It is also the most common form of cyanotic CHD with survival upto adulthood. However, TOF with both coronary and pulmonary vasculature anomalies is an extreme variant. We report a case of TOF with single coronary ostium (SCA); atretic branch pulmonary arteries and major aortopulmonary collateral artery (MAPCA) with relatively symptomless period upto 22 years of age.